Тираспольський укріплений район – заручник обставин (1941 р. ) - Коваль, М.В. (Історичний архів. Наукові студії, 2014)
Реконструйовано хід бойових дій в смузі Тираспольського укріпленого району влітку
1941 року та вказано причини його прориву. Реконструирован ход боевых действий в полосе Тираспольского укрепленного
района летом 1941 года и указаны причины его прорыва. Tiraspol fortified area was equipped on the left (eastern) bank of the Dniester river, from the mouth of the Yahorlyk river to Kuchurhansky estuary. The left (northern) flank of the fortified area bordered and closely interacted with the right (southern) flank of the Rybnytsya FA, the right (southern) near the town Mayaky was built on the Dniester estuary. The major operational areas of the fortified area were: Tiraspol – Zatyshshya station; Bendery – Tiraspol – Rozdilna station, both areas derive to the railroad Kyiv – Odesa. The data’ importance was determined with: dislocation of the Romanian army military units close to the border, broad valleys of the Reut and Byk rivers, the outputs of which are covered with gardens and forests, that allowed the enemy to come hiddenly to the Dniester, and to the dominant banks of the Dniester on the enemy’s side, the possibility to counteract with enemy’s land troops with its naval forces. Thus the fortified area covered an important strategic direction and took an important place in the southern defense complex of Stalin line, built on the river Dniester.